The Effectiveness of Zoom Meeting Application and Comedy Film Media on Students’ Anecdot Writing Ability - Ade Siti Haryanti; Achmad Hufad; Maman Fathurrohman (Hortatori : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2021)
The purpose of this research: (1) to know the effectiveness of zoom meeting application on the ability to write anecdotes. (2) to know the influence of comedy film media on the ability to write anecdotes. (3) to know the influence if the interaction of zoom meeting application and comedy film media together on the ability to write anecdotes. The research is a quantitative with the type used is experimental study using a 2x2 factorial design. This design used to examine two independent variables (zoom meeting application and Comedy Film Media) against one dependent variable (writing anecdotes) with the help of SPSS version 16 for windows application. The sample of the research as many as 40 students and take a sample random technique. Data collection was done by means of a student's writing ability test. The findings of the researcher indicate that: (1) there is a significant influence of students using the zoom meeting application on the ability to write anecdotes, with the acquisition value F0 = 5,415 and sig. = 0,026 ≤ 0,05; (2) there is a significant of students using the comedy film media on the ability to write anecdotes, with the acquisition value 11.094 and sig. = 0,02 ≤ 0,05; (3) there is no significant effect of the zoom meeting application and comedy film media on students’ anecdotes writing skills, with the acquisition value F0 = 1.518 and sig. = 0,226 ≥ 0,05.Keywords: Zoom Meeting Aplication, Comedy Film, Writing Ability